PENGARUH MANAJEMEN LABA PADA NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Lesmana, I Putu Adi Surya; Sukartha, I Made (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
One objective of the establishment of the firm is to maximize the firm’s value. Process of maximizing the firm’s value always disturbed due to the agency problem between shareholders and manager. The manager always tries to maximize his personal wealth and will perform earnings management. Earnings management is how to manipulate earnings by maximization the earning and minimized the earning to obtain certain advantages. The purpose of this research was to obtain empirical evidence of the impact earnings management by income increasing and income decreasing on firm’s value. The population in this research is manufacturing companies listed in Indonesia Stock Exchange in 2012-2015. Samples were selected using purposive sampling techniques and selected 123 companies. This study used a simple linear regression analysis. The results show that earnings management by income increasing has positive impact on firm’s value. While the earnings management by income decreasing has negative impact on firm’s value.
Keywords: firm’s value, earnings management, income increasing, income decreasing